Neutrophil nicotinamide adenine dinucleotide phosphate oxidase assembly. Translocation of p47-phox and p67-phox requires interaction between p47-phox and cytochrome b558. - Heyworth, P G (1991)
Two of the cytosolic NADPH oxidase components, p47-phox and p67-phox, translocate to the plasma membrane in normal neutrophils stimulated with phorbol myristate acetate (PMA). We have now studied the translocation process in neutrophils of patients with chronic granulomatous disease (CGD), an inherited syndrome in which the oxidase system fails to produce superoxide due to lesions affecting any one of its four known components: the gp91-phox and p22-phox subunits of cytochrome b558 (the membrane-bound terminal electron transporter of the oxidase), p47-phox, and p67-phox. In contrast to normal cells, neither p47-phox nor p67-phox translocated to the membrane in PMA-stimulated CGD neutrophils which lack cytochrome b558. In one patient with a rare X-linked form of CGD caused by a Pro----His substitution in gp91-phox, but whose neutrophils have normal levels of this mutant cytochrome b558, translocation was normal. In two patients with p47-phox deficiency, p67-phox failed to translocate, whereas p47-phox was detected in the particulate fraction of PMA-stimulated neutrophils from two patients deficient in p67-phox. Our data suggest that cytochrome b558 or a closely linked factor provides an essential membrane docking site for the cytosolic oxidase components and that it is p47-phox that mediates the assembly of these components on the membrane.